Réponses

2013-07-30T21:43:25+02:00

Développer et reduire D + Factoriser D :

 

D  =  (x + 5)² − 7x (x + 5)

     =  x² + 10x + 25 − 7x² − 35x

     =  −6x² − 25x + 25

 

     =  (x + 5)² − 7x (x + 5)     

     =  (x + 5) (x + 5 − 7x)

     =  (x + 5) (−6x + 5)

 

Factorise et réduit F :

 

F  =  (x + 1)² − (x − 1)²

    =  [ (x + 1) + (x − 1) ] [ (x + 1) − (x − 1) ]

    =  (2x) (2)

    =  4x

 

Factoriser E :

 

(9 − 12x + 4x²) − 4  =  (3 − 2x)² − 2²

                                   =  [ (3 − 2x) + 2 ] [ (3 − 2x) − 2 ]

                                   =  (5 − 2x) (1 − 2x)